The relations between innovativeness, market orientation and sucess among industrial firms in Poland - Łobos, Krzysztof; Szewczyk, Mirosława (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2018)
The main goal of this article is to analyze the relations in medium-sized and large industrial firms in Poland between the innovativeness, market orientation and success. In order to achieve this aim, a model of the dependencies between these factors is presented, together with an assessment of the significance and influence of innovation and market orientation on the success of a firm. We consider the activities of firms in the fields of product innovation, process innovation, marketing innovation and organizational innovation, in accordance with The Oslo Manual: Guidelines for Collecting and Interpreting Innovation Data.. The qualitative concept of the success of a firm is used in place of the performance of a firm in strict economic terms. This study was carried out based on data from 7,267 mediumsized and large industrial firms active in Poland. The main conclusion of the article is that the path from product and process innovation to success arrives through organizational and marketing innovations. A firm’s market orientation is an important factor in determining its success. However, at the same time it exhibits a weak, negative influence on innovation in the fields of organizational and marketing innovation. This apparent contradiction results from the fact that in Poland the marketing orientation of a firm may depend on the activities of those in the sales department, rather than on the formal structure of this department. Moreover, such a market orientation (which depends on the individual approaches of employees) may counteract the motivation to create a costly formal system which would promote the market orientation of a firm
Argumenta Oeconomica, 2018, Nr 1 (40), s. 275-298
Keywords: innovation; market orientation; success; industrial firms; structural equation model